2018
DOI: 10.20344/amp.10275
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ruptured Abdominal Aortic Aneurysms: State of the Art

Abstract: RESUMOIntrodução: O tratamento endovascular do aneurisma da aorta abdominal roto tem sido progressivamente preferido pelos potenciais benefícios de curto-prazo. A maioria dos estudos observacionais revela uma vantagem na sobrevida imediata para o tratamento endovascular do aneurisma da aorta abdominal roto, relativamente à cirurgia convencional. Contudo, os ensaios clínicos randomizados até hoje realizados não suportam estes resultados. Esta revisão tem por objetivo comparar os resultados do tratamento endovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…But it has recently been reported that EVAR is effective for RAAA. 5,6 To perform EVAR, the vital signs should be stable and the anatomy of the aneurysm needs to be suitable for repair. Fujimura and colleagues reported that large retroperitoneal hematoma, such as the present case, is related to higher mortality after EVAR for RAAA.…”
Section: Discussionmentioning
confidence: 99%
“…But it has recently been reported that EVAR is effective for RAAA. 5,6 To perform EVAR, the vital signs should be stable and the anatomy of the aneurysm needs to be suitable for repair. Fujimura and colleagues reported that large retroperitoneal hematoma, such as the present case, is related to higher mortality after EVAR for RAAA.…”
Section: Discussionmentioning
confidence: 99%